Owned : how tech billionaires on the right bought the loudest voices on the left - Higgins, Eoin (Bold Type Books, 2025)
"Matt Taibbi used to take on the rich and powerful, but today, his reporting is crafted to please grievance-addicted American conservatives. Glenn Greenwald, whose reporting on the Snowden leaks arguably changed the course of history, has similarly taken a hard right turn. Yet these political transformations of journalists formerly associated with the left did not happen in a vacuum. The new mouthpieces of the right are paid and disseminated by an emerging "alternative" media ecosystem, funded by a cohort of billionaires whose goal is to censor critics, so these new plutocrats can pursue their businesses-and personal vendettas-entirely unimpeded. Owned is the story of the underreported collaboration between the new wealth and the new journalism. Right-wing billionaires like Marc Andreessen, David Sacks, Peter Thiel, and Elon Musk use their wealth to fund journalists-like Taibbi and Greenwald-who exploit the failings of traditional journalism and social media. This unholy alliance has undermined the very idea of an independent and fact-based press while ostensibly standing up for principles of liberty and free speech. A biting exposé of journalist greed and tech-billionaire ambition, Owned follows the money, and offers a chilling portrait of the future social media and news landscape, empty of all critique, except for newly empowered right-wing commentators"--